Analisis Pengembangan Bisnis Tamtam Thai Tea Di Bogor - Yohanes Sulistyadi; Petrus Benzen Gero (Jurnal Sains Terapan Pariwisata, 2021)
The reason the author taking this title because author want to try to develop this business in order to gain a wider market share, especially in Bogor. The author has belief that Tamtam Thai Tea can satisfy the tastes of consumers in general, especially in Bogor, although this kind of business in Bogor has mushroomed quite a lot, it does not diminish because the writer wants to compete in the beverage business. By paying attention to the weather in Bogor which is getting hotter because of the climate change, population increases, settlement increases, presumably the presence of Tamtam Thai Tea can be one of the choices of Bogor people’s taste that are very consumptive especially among children and adults. The owner of this business which is the author has been running this beverage business more than one year, since February 2019 until now. During this time period and basedon the SWOT, BEP,and PP analysis methods, it was concluded that this business was worthy to run. The author endeavors from the title of this thesis based on a case study on his own business namely Tamtam can develop enthusiasm especially for writers in developing small businesses towards macro businesses, can increase income in addition to the writer trying to get a job in another field, can open or add jobs, can meet tastes society and compete beverage business.